Drilling of titanium alloy (Ti6Al4V) – a review. Issue 4 (4th July 2021) - Yuan, Chua Guang; Pramanik, A.; Basak, A. K.; Prakash, C.; Shankar, S.
Abstract: In recent years, demand of titanium alloy (Ti6Al4V) in various industries especially aerospace industries drastically increased. Several exceptional properties of titanium alloy that contribute to its popularity include high compressive and tensile strength, fracture toughness oxidation resistance and high strength-to-weight ratio. However, due to these superior properties, titanium alloys are categorized as hard-to-machine materials. The drilling process is accounted for roughly 40%−60% of material removal processes of an aeronautical product. Drilling processes for titanium alloys are categorized into conventional method (twist drilling) and unconventional method (rotary ultrasonic machining [RUM] drilling, laser drilling and electron discharge machining [EDM] drilling). This research aims to identify mechanisms and limitations of each drilling method applicable on titanium alloys. In addition, processing parameters affecting performance measures of each drilling method are discussed. The main problem associated with conventional twist drilling is extreme processing temperature, resulting in rapid tool wear and extensive burrs formation. These issues cause the cost for titanium alloy drilling to be relatively high as compared with twist drilling of other materials. To minimize these issues, researchers have developed several unconventional drilling methods, aiming to minimize issues found in conventional twist drilling.